2023
DOI: 10.1186/s12889-023-15602-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of family-centred sexual health education and HPV self-sampling in promoting cervical cancer screening among hard-to-reach indian women in rural and tribal areas: a community-based pilot study

Abstract: Background While cervical cancer deaths have declined steeply in high-income countries due to the widespread use of the Papanicolaou test (Pap test), the same trend has not emerged in low or middle-income countries (LMICs). Access to screening in LMICs like India is limited due to barriers such as limited healthcare infrastructures, lack of sexual health education, and stigma demarcating sexually transmitted infections (STIs). HPV self-sampling (HPV-SS), a woman–centered and at-home method for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…For instance, our study observed advancements in participants' knowledge and attitudes about cervical cancer and screening, coupled with a reduction in STI stigma following their engagement in SHE sessions (overall mean difference in knowledge: z = 6.1 ± 2.4, p < 0.001; attitudes towards the Pap test: z = 2.2 ± 8.4, p < 0.001; STI stigma: z = 2.8 ± 12.4, p < 0.001). Among the 120 women enrolled in our study, 115 chose HPV-SS as the primary screening test, while 2 opted for Pap and 1 chose VIA testing, demonstrating an increase in screening participation [7].…”
Section: Opportunities and Solutionsmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, our study observed advancements in participants' knowledge and attitudes about cervical cancer and screening, coupled with a reduction in STI stigma following their engagement in SHE sessions (overall mean difference in knowledge: z = 6.1 ± 2.4, p < 0.001; attitudes towards the Pap test: z = 2.2 ± 8.4, p < 0.001; STI stigma: z = 2.8 ± 12.4, p < 0.001). Among the 120 women enrolled in our study, 115 chose HPV-SS as the primary screening test, while 2 opted for Pap and 1 chose VIA testing, demonstrating an increase in screening participation [7].…”
Section: Opportunities and Solutionsmentioning
confidence: 90%
“…While cervical cancer is highly preventable through early detection and treatment, LMICs struggle to adopt preventive measures due to limited healthcare infrastructure, sociocultural factors (modesty, male dominance in making decisions about family matters, etc. ), social stigma surrounding sexually transmitted infections, limited knowledge about cervical cancer and screening, and a lack of female healthcare providers [4][5][6][7]. As a result, screening coverage in LMICs is only 19%, compared to 63% in high-income countries [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the role of education in overcoming many of the barriers at the individual level cannot be ignored. Delivery of education through peer educators has also been shown to increase the acceptability and uptake of cervical cancer screening ( 40 , 41 ). According to findings from a systematic review by Makadzange et al the use of peer educators and culturally sensitive and tailored material significantly impacted the delivery of educational messages for cervical cancer prevention to the target population in Africa ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to findings from a systematic review by Makadzange et al the use of peer educators and culturally sensitive and tailored material significantly impacted the delivery of educational messages for cervical cancer prevention to the target population in Africa ( 40 ). Similarly, a study conducted in India also supports using culturally appropriate educational material and interventions to reach communities and promote the uptake of cervical cancer screening especially among rural communities where the lack of education is the major hurdle to increased screening uptake among women ( 41 ).…”
Section: Discussionmentioning
confidence: 99%